Hiperaktivitas Saraf Simpatis Dan Kadar Nitrat Okside Pada Ibu Hamil Terhadap Dinamika Tekanan Darah - Meli Doloksaribu (EMBRIO: Jurnal Kebidanan, 2022)
Hypertension is a complication that most often occurs in pregnancy (5-10% of pregnancies). About 30% of hypertension is caused by chronic hypertension and 70% is caused by gestasional pre-eclampsia hypertension. Blood pressure is a hemodynamic parameter that is simple and easy to measure. Blood pressure describes a person’s hemodynamic situation. Studies show that the sympathetic nervous system plays an important role in the pathogenesis of hypertension, namely an increase in the activity of the sympathetic nervous system. The autonomic nervous system causes vasoconstriction and arterial dilatation to maintain blood pressure. The study aimed to determine the levels of nitric oxide and sympathetic nerve hyperactivity. This study used a prospective cohort study design. To assess the hyperactivity of the sympathetic nerves, a Cold Pressor Test was performed and the levels of Nitric Oxide were examined for blood serum samples using the Elisa Kit. Where the measurement is carried out once, namely during the second trimester of pregnancy, while the blood pressure of pregnant women is measured once a week and followed up to 24 weeks of gestation. The number of samples was 40 pregnant women who were selected by consecutive sampling. Data collection was carried out according to data collection procedures. The data obtained in a prospective cohort were used statistical analysis of the Mann Whitney test to see the relationship or correlation between Sympathetic Nerve Hyperactivity and Nitric Oxide Levels and Blood Pressure Dynamics. The results showed that the mother was hyperreactor (12.44 ± 5.811) and mother was normoreactor (10.46 ± 3.215). Bivariate analysis showed that there was no significant difference between sympathetic nerve hyperactivity and nitric oxide levels (p=0.172). It was concluded that sympathetic nerve activity did not have a significant relationship with the increase in nitric oxide levels.